Global burden and trends of adverse effects of medical treatment, 1990–2021: an analysis from the global burden of disease study 2021 - Zhang, Keqing; Gao, Yuhai; Lu, Yunfei (Frontiers in Pharmacology, 2025)
BackgroundAdverse effects of medical treatment (AEMT) pose a significant global health concern, yet prior studies have mostly focused on specific adverse events or single countries, leaving the long-term global epidemiological patterns insufficiently characterized. As healthcare utilization grows, it is crucial to comprehensively quantify the global, regional, and national burden of AEMT and to forecast future trends for effective resource allocation and quality improvement.MethodsWe utilized data from the Global Burden of Disease (GBD) study 2021. AEMT were defined based on GBD criteria, and incidence, prevalence, deaths, and disability-adjusted life years (DALYs) data were extracted. This study was stratified by age, gender, region and socio-demographic index (SDI), and estimated annual percentage change was used to assess the trends from 1990 to 2021. Based on SDI, we conducted health inequality analysis and used the Bayesian age-period-cohort model to predict the trend changes over the next 15 years.ResultsGlobally, there were 12,481,276 new cases of AEMT, with 122,330 deaths, resulting in 4,846,981 DALYs loss in 2021. The age-standardized incidence (ASIR) and prevalence rates (ASPR) worldwide were showing an upward trend, especially in high SDI regions. Both age-standardized mortality (ASMR) and DALYs rates (ASDR) showed a gradual decline during the study period, but they still carried a heavy burden in the low SDI regions (2021 ASDR: 3.71 [95% UI: 2.90 to 5.68] per 100,000 persons-year; 2021 ASR for DALYs: 150.37 [95% UI: 109.08 to 215.24] per 100,000 persons-year). Australasia demonstrated the highest ASIR and ASPR, while Western Sub-Saharan Africa showed the highest ASMR and ASDR. Health inequality analyses revealed that both absolute and relative inequalities of DALYs were narrowing. By 2036, it is forecast that ASIR will decrease to 72.33 (19.40–125.27) per 100,000 persons-year, and ASDR will decrease to 40.98 (21.52–60.43) per 100,000 persons-year.ConclusionThis study provided a comprehensive global, regional, and national assessment of the burden and inequality of AEMT over the past three decades, coupled with forecasts to 2036. The findings revealed distinct epidemiological patterns across SDI levels and regions, filling an important knowledge gap and offering evidence to guide healthcare safety strategies, medical education, and surveillance systems to further reduce the burden of AEMT worldwide.